Formulation Development And Evaluation Of Liquisolid Compacts For Ibuprofen Liquisolid Tablets (Journal of Pharmaceutical Negative Results, 2023)
Poor aqueous solubility and slow dissolution rate adversely affect the bioavailability of ibuprofen. The purpose of the investigation was to develop and evaluate liquisolid compact to improve the dissolution rate of the poorly soluble drug ibuprofen. Mathematical models were used to develop different liquisolid compacts. The calculated required quantities of microcrystalline (carrier), aerosil 200 (coating material), sodium starch glycolate (disintegrant) and cremophor RH 40, and kolliphor p 188 (non-volatile liquid vehicle) were used to produce acceptably flowable and compressible admixture. FTIR and DSC studies showed the compatibility among the excipients and drug. The tablets were developed by the direct compression method. The formulated liquisolid tablets were evaluated for weight variation, hardness, friability, disintegration time, drug content, and in vitro release characteristics of the ibuprofen. The tableting properties of the liquisolid compacts were within acceptable limits. The formulation (LS6) showed complete drug release within 60 min. Dissolution data treatments (Q15, IDR, RDR, DE) showed better drug release (LS6) than pure drug and marketed formulation. The t-test indicated a statistically significant difference in the dissolution profiles between LS6 and marketed formulation. The liquisolid technique proved the success of improving the dissolution of a poorly soluble drug like ibuprofen.